Comprehensive autoantibody profiling in systemic autoimmunity by a highly-sensitive multiplex protein array - Kuzumi, Ai; Norimatsu, Yuta; Matsuda, Kazuki M.; Ono, Chihiro; Okumura, Taishi; Kogo, Emi; Goshima, Naoki; Fukasawa, Takemichi; Fushida, Natsumi; Horii, Motoki; Yamashita, Takashi; Yoshizaki-Ogawa, Asako; et al. (Frontiers in Immunology, 2023)
Comprehensive autoantibody evaluation is essential for the management of autoimmune disorders. However, conventional methods suffer from poor sensitivity, low throughput, or limited availability. Here, using a proteome-wide human cDNA library, we developed a novel multiplex protein assay (autoantibody array assay; A-Cube) covering 65 antigens of 43 autoantibodies that are associated with systemic sclerosis (SSc) and polymyositis/dermatomyositis (PM/DM). The performance of A-Cube was validated against immunoprecipitation and established enzyme-linked immunosorbent assay.Further, through an evaluation of serum samples from 357 SSc and 172 PM/DM patients, A-Cube meticulously illustrated a diverse autoantibody landscape in these diseases. The wide coverage and high sensitivity of A-Cube also allowed the overlap and correlation analysis between multiple autoantibodies. Lastly, reviewing the cases with distinct autoantibody profiles by A-Cube underscored the importance of thorough autoantibody detection. Together, these data highlighted the utility of A-Cube as well as the clinical relevance of autoantibody profiles in SSc and PM/DM.